Successful treatment by chemoradiotherapy for locally advanced cervical low-grade endometrial stromal sarcoma. Case report and review of the literature - Moszynska-Zielinska, Malgorzata; Gottwald, Leszek; Spych, Michal; Bigos, Ewelina; Zytko, Leszek; Kowalczyk–Amico, Katarzyna; Fijuth, Jacek (European Journal of Oncology and Environmental Health, 2015)
We describe the case of a 51-year-old patient with primary low-grade endometrial stromal sarcoma (ESS) of the uterine cervix (FIGO stage IIB). The patient was diagnosed with the neoplasm in June 2009. No synchronous extra-pelvic metastases were found. She was referred to chemoradiotherapy. Three cycles of AP-scheme (doxorubicin 60 mg/m2 and cisplatine 50 mg/m2; one cycle every 28 days) were administrated. External beam irradiation was divided into two steps. In the first step the uterus, both adnexa, parametria, and regional pelvic lymph nodes were irradiated (total dose of 39.6 Gy, 4 fields, 22 fractions of 1.8 Gy per fraction, 5 days/week). Afterwards, only the uterus and both adnexa were irradiated (total dose of 26.0 Gy, 3 fields, 13 fractions of 2.0 Gy per fraction, 5 days/week). As the last part of treatment, intracavitary brachytherapy was administered using a high-dose Ir192 source, with 7 Gy/2.0 cm being delivered to the vaginal surface in 1 fraction (intrauterine applicator 6 cm in diameter with vaginal cylinder 2.6 cm). Treatment was finished in January 2010. The patient, 57 months after the end of treatment, is still under control in our department. No signs of recurrence have been detected since then. We conclude that patients with primary low-grade ESS of the uterine cervix, even when locally advanced, can be successfully treated with combined chemoradiotherapy.